Detection of Toxoplasma gondii oocysts in soil and risk mapping in an island environment in the Northeast of Brazil. Issue 6 (30th September 2022) - de Oliveira, Pollyanne Raysa Fernandes; de Melo, Renata Pimentel Bandeira; de Oliveira, Umberto Diego Rodrigues; Magalhães, Fernando Jorge Rodrigues; Junior, Rivaldo José Ferreira; Andrade, Müller Ribeiro; Mota, Rinaldo Aparecido
Abstract: Toxoplasmosis is an emerging and re‐emerging infectious disease that can be transmitted through a contaminated environment. Environmental contamination is an emergency health issue, and determining its occurrence is fundamental to a One Health approach. In this study, we addressed the extent of environmental contamination and viability of Toxoplasma gondii oocysts in soil in different environments on Fernando de Noronha Island, Brazil. In addition, we performed species distribution modelling to predict the environmental suitability for coccidia persistence in the studied area. Soil samples were collected in 14 neighbourhoods of the Island and in the four main squares, creating a total of 95 soil samples (five samples per site). The samples were analyzed by the polymerase chain reaction (PCR) technique for the presence of the 18S ribosomal DNA gene of Apicomplexan protozoa, followed by genetic sequencing. We obtained 4.2% (4/95) positive soil samples with 100% similarity for T. gondii sequences. Two out of four positive sites on PCR showed viability of T. gondii oocysts through the mouse bioassay technique. As a result of the application of the species distribution modelling, environmental adequacy for the coccidia was observed throughout the Island. The results confirm the contamination of the soil in this insular environment by T. gondii oocysts and the environmental suitability by modelling application. These findings are an alert for the possibility of infection in animals and humans by contaminated soil, and for contamination of the maritime environment in addition to water resources for consumption by the local population.